Metaniche session 2016: Tailor-made sensors for rapid Therapeutic Drug Monitoring-Interactions between Biomaterial Physicists, Chemical Engineers and Clinicians for successful translation of technologies in Healthcare - Yoshimi, Yasuo; Pushkala, Subramanian; Vijaykumar, Harikrishnan; Dedeepiya, Vidyasagar Devaprasad; Ignacy, Arockyaa; Swaminathan, Jose; Rajmohan, Mathaiyan; Karthick, Ramalingam; Abraham, Samuel Jk (Journal of stem cells & regenerative medicine, 2016)
The Metaniche session is an academic session conducted as a part of Nichi-In Centre for Regenerative Medicine (NCRM)’s novel Initiatives' Conclave in Healthcare Every year (NICHE), the ‘NCRM NICHE’ organized every year in the month of October by Nichi-In Centre for Regenerative Medicine (NCRM), an Indo-Japan academic Institute based at Chennai, India. The Metaniche session aims to bring together the realms of Physics, Chemistry and Biology by portraying inventions or discoveries in physical and chemical sciences which are in the pipeline with high application potential in biology and healthcare. The Metaniche session-2016, held on 22nd October, 2016 in Chennai, India was on the application of biomaterial-based sensors for application in rapid therapeutic drug monitoring (TDM) systems. The session focussed on the role of biomaterials in medicine giving an overview and history of the evolution of biomaterials to suit the growing needs in medicine, followed by emphasizing the need for rapid TDM systems. The final part portrayed the development of tailor-made sensors for rapid TDM using molecularly imprinted polymers as given below. Biomaterials and Medicine It has been always medical practitioners coming first to identify the need to lead themselves and others towards the best therapy. When patient services emerged, the clinicians themselves were everybody. Dr Gibbon, when he did his first open heart case in 1950’s, he was the perfusionist and perhaps anaesthetist too. To get into its (bio) materials, through a case study, let us take a review of a simple clinical procedure. Wound closure through suturing. Its tribology matrix highlighted below (Figure 1), sketches its journey, clinical demands, scientific solutions and biomaterials thereof. The bottom line, best is still (re)searched.